Microfluidic-assisted cyclic mechanical stimulation affects cellular membrane integrity in a human muscular dystrophy in vitro model. Issue 119 (17th November 2015) - Michielin, F.; Serena, E.; Pavan, P.; Elvassore, N.
Abstract : The development of a microfluidic-based cell stretching device allows to investigate membrane permeability during cyclic mechanical stimulation in a human Duchenne Muscular Dystrophy skeletal muscle in vitro model. Abstract : Cyclic mechanical stimulation has been found to deeply affect cell behavior in terms of cytoskeleton remodeling, signaling pathway alteration and differential gene expression in several diseases. In Duchenne Muscular Dystrophy (DMD), characterised by a lack of the protein dystrophin, which plays a structural and regulatory role in preserving membrane integrity and homeostasis, mechanical stress seems to enhance the pathogenesis of muscle fibers, as indicated in many studies on mdx, a DMD mouse model. In this study we aimed to investigate if the lack of dystrophin results in impairment of membrane integrity after prolonged cyclic mechanical stimulation in a human in vitro model. We developed an ad hoc microfluidic-based cell-stretching device in order to apply defined external stimuli, in terms of both frequency and intensity, to primary myoblast and myotube cell cultures. Computational modeling supported the design of the device, in order to estimate the mechanical state induced in the cells. Both static and cyclic (1 Hz) mechanical stretches for 2 h on myoblasts result in frequency-dependent cytoskeletal actin filament remodeling along the direction of minimum strain. On the other hand, an over physiological stretch stimulation (20% strain) results in localized membrane impermeant marker uptake due to loss of membrane integrity. Interestingly, the results show that human myotubes are more sensitive to mechanical stretching than myoblasts. Thanks to the developed technology we were able to investigate how cyclic stretching affects the membrane permeability of both healthy and dystrophic myotubes. The results show that DMD myotubes have a higher stretch-induced membrane permeability compared to healthy myotubes, when both are subjected to 90 min cyclic strain of 15%. Interestingly, the same effect was not observed after only 45 min of the same cyclic strain. We also investigated the implication of increased stretch-dependent membrane permeability in the activation of the calcium dependent protease calpain-2, which is recognized to be aberrantly expressed in dystrophic myotubes. This microfluidic approach allows accurate and temporally defined mechanical stimulation at the single or subcellular level. Moreover, it could be used to study early pathologic events and potential therapeutic approaches on a skeletal muscle disease in vitro model subjected to stress conditions normally experienced by muscle fibers in vivo .